SINTESIS SENYAWA ANTIMALARIA BARU TURUNAN FENANTROLIN N-(2-NITROBENZIL)-1,10-FENANTROLINIUM IODIDA DAN (1) N-(4-NITROBENZIL)-1,10-FENANTROLINIUM IODIDA - Dwi Utami; Iin Narwanti; Jumina Jumina (Molekul, 2014)
Malaria is a global health problem, especially in the tropics. Efforts to decrease the incidence of malaria plagued the plasmodium resistance to existing antimalarial drugs. Benzyl Phenanthrolium Iodide derivates have been proved has antimalarial activity. The aim of this study is synthesis the nitro benzyl phenanthrolium.The research that has been done was the synthesis of (1)-N-(2-nitrobenzyl) phenantrolium iodide and(1)-N-(4-nitrobenzyl)-1,10-phenantrolium iodide. Synthesis of (1)-N-(2-nitrobenzyl)-1,10-phenantrolium iodide through a two-steps reaction SN-2 is the reaction of (1)N-(2- nitrobenzyl) chloride and potassium iodide followed by reaction phenantroline 1:10 monohydrate, whether the second product was 4-nitrobenzil bromida as starting material. The reaction were started by reflucting the nitro subtituted benzil halida with potassium iodide for 1 hour, yielded nitro subtituted benzyl iodide. Then followed by reflucting nitro substituted benzyl iodide with 1,10-phenanthroline for 11 hours. The final product isolated and purificated by suitable solvent. The melting point was conducted by melting poin apparatus. The structures of product was characterized by IR and UV-Vis spectroscopy.Results obtained in the form of thick liquid light yellow with a melting point of 54.2-63.5oC. While the compound (1)-N-(4-nitrobenzyl)-1,10-phenantrolium iodide is synthesized from 4-nitrobenzylbromide and potassium iodide followed by reaction phenantroline 1:10 monohydrate. Synthesis results in the form of pale yellow crystals with a melting point of 221–225oC . The resulting yield of 32.87%. The interpretation of UV-Vis and Infra red spectras indicated that nitro benzyl iodide have been condensed with 1,10 phenantroline as the end of the product.